Real-Time Acoustic Telemetry Buoys as Tools for Nearshore Monitoring and Management - James M. Anderson; Brian S. Stirling; Patrick T. Rex; Emily A. Spurgeon; Anthony McGinnis; Zachariah S. Merson; Darnell Gadberry; Christopher G. Lowe (Journal of Marine Science and Engineering, 2026)
Acoustic telemetry monitoring for tagged sharks in nearshore waters has become an important tool for beach safety management; however, detection performance can vary widely in shallow, high-energy nearshore environments where management decisions are often most time-sensitive. Real-time acoustic telemetry buoys offer the potential to deliver live detections and system diagnostics, but their performance relative to autonomous bottom-mounted receivers remains poorly evaluated under realistic coastal conditions. We compared the detection efficiency of real-time buoy-mounted acoustic receivers and autonomous bottom-mounted receivers across five nearshore sites in southern California. Using paired long-term reference tag deployments and short-term range tests, we quantified detection probability, effective detection range, and the influence of environmental conditions and receiver placement. Detection performance was evaluated in relation to wind speed, water temperature, receiver tilt, and signal-to-noise ratio. Both buoy-mounted and bottom-mounted receivers maintained high long-term detection efficiency, recovering 77–99% of expected transmissions at 82–250 m. Range tests indicated greater effective detection distances for buoy-mounted receivers, with 50% detection probabilities occurring at approximately 471 m compared to 282 m for bottom-mounted receivers. Receiver placement strongly influenced performance, with surface-mounted receivers outperforming bottom-mounted units regardless of receiver model. Environmental effects on detections were site-specific and variable. Detection probability varied predictably with environmental conditions. Higher SNR increased detection success, particularly for bottom/substrate mounted receivers, while warm water significantly reduced detection probability across placement configuration. These results demonstrate that real-time acoustic telemetry buoys provide reliable detection performance in dynamic nearshore environments while offering key operational advantages, including immediate data access and system diagnostics. The observed relationships demonstrate that receiver performance is dynamic rather than fixed, and that real-time buoy systems therefore represent a practical tool for coastal monitoring programs that require timely information to support adaptive management, public safety, and conservation decision making.

eDNA metabarcoding detection of nearshore juvenile white sharks (Carcharodon carcharias) and prey fish communities - Zachariah S. Merson; Elizabeth E. Jahn; Matthew A. Barnes; Emily A. Spurgeon; Patrick T. Rex; Jack T. Elstner; Yamilla N. Samara Chacon; James M. Anderson; Whitney D. Jones; Christopher G. Lowe (Journal of Experimental Marine Biology and Ecology, 2025)

The influence of micro-scale thermal habitat on the movements of juvenile white sharks in their Southern California aggregation sites - Emily Spurgeon; Marten L. Thompson; Mitchell D. Alexander; James M. Anderson; Patrick T. Rex; Brian Stirling; Kevin Abbott; Christopher G. Lowe (Frontiers in Marine Science, 2024)
While juvenile white sharks (JWS) can display regional endothermy, the need to maintain internal temperatures within an energetically favorable range likely drives thermoregulatory movements to maximize growth and foraging efficiency. Many JWS from the northeastern Pacific population aggregate seasonally in nearshore nursery habitats throughout the Southern California Bight and historic data show that inter-seasonal movement patterns may be heavily dependent on ambient water temperature. However, the degree to which micro-scale (e.g., ~10 m 2 ) water temperature heterogeneity influences JWS three-dimensional movement within nearshore aggregation sites is unknown. High-resolution temperature and passive acoustic-telemetry geo-positional data were used to quantify how temperature and vertical thermal stratification influenced JWS movement using several modeling approaches. JWS selected for water temperatures between 16 – 22°C and depths shallower than 2 m. Sharks occupied deeper waters during dawn and dusk periods, and their distance from the seafloor and spatial orientation of their depth distribution was significantly related to the thermal structure of the water column across the monitored area. Tagged sharks remained above a 16°C thermal threshold and altered their horizontal and vertical distributions accordingly. While high-resolution movement and environmental data provide improved predictability of micro-scale habitat use and distribution, other variables such as prey distribution, behavior, and competition would further improve habitat use models for this highly mobile species.

Evidence of increasing juvenile white sharks ' ( Carcharodon carcharias ) habitat use at the Northern Channel Islands - Ryan M. Freedman; James M. Anderson; Chris Caldow; Brian Stirling; Patrick Rex; Emily Spurgeon; Steve McCullough; Kady Lyons; Jack May; Connor F. White; Ryan K. Logan; Emily Meese; et al. (Journal of Fish Biology, 2023)
Juvenile white sharks ( Carcharodon carcharias ) typically aggregate along coastal beaches; however, high levels of recruitment and shifting oceanographic conditions may be causing habitat use expansions. Telemetry data indicate increased habitat use at the Northern Channel Islands (California, USA) by juvenile white shark that may be in response to increased population density at aggregation locations, or anomalous oceanographic events that impact habitat use or expand available habitat. Findings illustrate the need for long‐term movement monitoring and understanding drivers of habitat use shifts and expansion to improve ecosystem management.

Reciprocal testcross design for genome-wide prediction of maize single-cross performance - Patrick K. Sweet; Rex Bernardo (Theoretical and Applied Genetics, 2023)

Improved Growth and High Inheritance of Melanocortin-4 Receptor (mc4r) Mutation in CRISPR/Cas-9 Gene-Edited Channel Catfish, Ictalurus punctatus - Michael Coogan; Veronica Alston; Baofeng Su; Karim Khalil; Ahmed Elaswad; Mohd Khan; Andrew Johnson; De Xing; Shangjia Li; Jinhai Wang; Rhoda M. C. Simora; Cuiyu Lu; et al. (Marine Biotechnology, 2022)

Observations of a species‐record deep dive by a central Pacific female scalloped hammerhead shark ( Sphyrna lewini ) - James M. Anderson; Patrick T. Rex; Kelsey Maloney; Mark Johnston; Deron Verbeck; Neil Allen; Kim Holland (Journal of Fish Biology, 2022)
A female scalloped hammerhead shark ( Sphyrna lewini ) conducted a species record deep dive to 1240 m in coastal‐pelagic waters off Hawaii Island. This extends the deepest known depth range of the species by over 200 m (650 ft) and highlights the question of the extent to which deep‐diving activity is mediated by physiological constraints, such as temperature and oxygen availability.

Non-random Co-occurrence of Juvenile White Sharks (Carcharodon carcharias) at Seasonal Aggregation Sites in Southern California - James M. Anderson; Alyssa J. Clevenstine; Brian S. Stirling; Echelle S. Burns; Emily N. Meese; Connor F. White; Ryan K. Logan; John O’Sullivan; Patrick T. Rex; Jack May; Kady Lyons; Chuck Winkler; et al. (Frontiers in Marine Science, 2021)
Many terrestrial and aquatic taxa are known to form periodic aggregations, whether across life history or solely during specific life stages, that are generally governed by the availability and distribution of resources. Associations between individuals during such aggregation events are considered random and not driven by social attraction or underlying community structure. White sharks ( Carcharodon carcharias ) have been described as a species that exhibits resource-driven aggregative behaviors across ontogenetic stages and juvenile white sharks are known to form aggregations at specific nursery sites where individuals may remain for extended periods of time in the presence of other individuals. We hypothesized juvenile white sharks form distinct communities during these critical early phases of ontogeny and discuss how a tendency to co-occur across life stages may be seeded by the formation of these communities in early ontogeny. We present results from a series of social network analyses of 86 juvenile white sharks derived from 6 years of passive acoustic telemetry data in southern California, demonstrating the likelihood of association of tagged juvenile white sharks is greater when sharks are of similar size-classes. Individuals in observed networks exhibited behaviors that best approximated fission-fusion dynamics with spatiotemporally unstable group membership. These results provide evidence of possible non-resource driven co-occurrence and community structure in juvenile white sharks during early life stages.